Description of a second specimen of Leptotyphlops parkeri (Squamata: Leptotyphlopidae), with comments on its generic placement - Boundy, Jeff (Zootaxa, 2012)
All but two of the 121 species of the snake family Leptotyphlopidae are characterized by possessing 14 scale rows around the body throughout most of its length. The exceptions, both possessing 16 scale rows, are Rhinoleptus koniagui (Villiers) of the Guinean region, and Leptotyphlops parkeri Broadley, known from one specimen from Ethiopia. According to Adalsteinsson et al. (2009), some leptotyphlopids from the West Indies may possess 16 scale rows, but their statement was based on an unpublished work (Wallach, 1998) and an original source for the scale row count could not be found (B. Hedges, V. Wallach, pers. comm.). During a check of snake identifications at the Louisiana State University Museum of Natural Science (LSUMZ), I encountered a specimen of Leptotyphlops from Kenya that had 16 scale rows, and closely resembled L. parkeri in arrangement of the cephalic scales (Fig. 1). Collection data for LSUMZ 53772 are: Tsavo National Park, [most probably from Kilaguni Lodge,] Coast Province, Kenya, collected December 1972 by Harold A. Dundee. The habitat at Kilaguni Lodge is referred to Acacia–Commiphora deciduous bushland and thicket (R. Drewes, pers. comm.). The snake was collected on the ground at night (H.A. Dundee, pers. comm.).